Analysis space-time covrage of vegetable, Caetés Country-PE, through of NDVI image data - Bernardo, Wilson dos Santos; Lima, Carlos Eduardo Santos de; Santos, Ezequiel de Melo; Silva, Diego Vieira da; Gomes, Daniel Dantas Moreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The use of remote sensing has been widely used by researchers. In order to get better results on the constant dynamics of vegetation cover. This paper presents a space-temporal analysis, using Normalized Difference Vegetation Index (NDVI), through the use of GIS and Remote Sensing techniques, using images related to the years 1994, 2000 and 2010. The methodology used is the prospecting literature and the treatment of remote sensing images, were used images of the satellite TM / Landsat 5, after correction of the images was calculated from NDVI, to make it possible to classify the vegetation and prepare the maps and get the data about the distribution of vegetation throughout the area Caetés-PE municipality. After this step, the graphicsand tables were produced that allowed a comparative analysis between vegetation indicesrelated to eac hyear studied.